Development of an experimental model of burst fracture with damage characterization of the vertebral bodies under dynamic conditions. (November 2017) - Germaneau, A.; Vendeuvre, T.; Saget, M.; Doumalin, P.; Dupré, J.C.; Brémand, F.; Hesser, F.; Brèque, C.; Maxy, P.; Roulaud, M.; Monlezun, O.; Rigoard, P.
Abstract: Background: Burst fractures represent a significant proportion of fractures of the thoracolumbar junction. The recent advent of minimally invasive techniques has revolutionized the surgical treatment of this type of fracture. However mechanical behaviour and primary stability offered by these solutions have to be proved from experimental validation tests on cadaveric specimens. Therefore, the aim of this study was to develop an original and reproducible model of burst fracture under dynamic impact. Methods: Experimental tests were performed on 24 cadaveric spine segments (T11-L3). A system of dynamic loading was developed using a modified Charpy pendulum. The mechanical response of the segments (strain measurement on vertebrae and discs) was obtained during the impact by using an optical method with a high-speed camera. The production of burst fracture was validated by an analysis of the segments by X-ray tomography. Findings: Burst fracture was systematically produced on L1 for each specimen. Strain analysis during impact highlighted the large deformation of L1 due to the fracture and small strains in adjacent vertebrae. The mean reduction of the vertebral body of L1 assessed for all the specimens was around 15%. No damage was observed in adjacent discs or vertebrae. Interpretation: With this new, reliable and replicable procedure for production and biomechanical analysis of burst fractures, comparison of different types of stabilization systems can be envisaged. The loading system was designed so as to be able to produce loads leading to other types of fractures and to provide data to validate finite element modelling. Highlights: A specific experimental dynamic setup for spinal loading has been developed. A biomechanical analysis was performed during impact on spines from a dynamic optical method. Mechanical effects of a dynamic impact on spine were characterized by X-ray imaging and optical analysis. A reproducible model of burst fracture on human cadaveric specimens was developed.